2017
DOI: 10.1093/cid/cix762
|View full text |Cite
|
Sign up to set email alerts
|

Early Fecal Microbiota Transplantation Improves Survival in Severe Clostridium difficile Infections

Abstract: Early FMT dramatically reduces mortality and should be proposed as a first-line treatment for severe CDI. Further studies are needed to clarify complications and contraindications. Surgery should be reassessed in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 43 publications
5
79
0
2
Order By: Relevance
“…By utilising both the CCI and IDSA/SHEA guidelines, we were able to objectively classify patients regarding the severity of their CDI as well as their global illness severity. One prior study observed a similar mortality benefit for early FMT in patients with severe CDI but did not include patients with fulminant CDI and had a median CCI of 2, indicating a less severe cohort of patients …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…By utilising both the CCI and IDSA/SHEA guidelines, we were able to objectively classify patients regarding the severity of their CDI as well as their global illness severity. One prior study observed a similar mortality benefit for early FMT in patients with severe CDI but did not include patients with fulminant CDI and had a median CCI of 2, indicating a less severe cohort of patients …”
Section: Discussionmentioning
confidence: 90%
“…While the average time to FMT in our study was 9 days, it is possible that earlier time to FMT could have improved survival rates. In one retrospective study, early FMT (defined as 2‐4 days after initiating antibiotics) was associated with improved mortality in severe CDI …”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of FMT in critically ill patients occurred mostly in the context of CDI, where 1 in 10 patients with CDI requires care in an ICU or colectomy, or dies from CDI . The 2 largest cohort studies to date and the only RCT for severe CDI reported no serious adverse events attributable to FMT in a total of 91 patients with severe‐complicated CDI who received FMT . There does not appear to be an observed increase in risk for perforation attributable to colonoscopy‐delivered FMT.…”
Section: Discussionmentioning
confidence: 94%
“…37 The 2 largest cohort studies to date and the only RCT for severe CDI reported no serious adverse events attributable to FMT in a total of 91 patients with severe-complicated CDI who received FMT. [38][39][40] There does not appear to be an observed increase in risk for perforation attributable to colonoscopy-delivered FMT. Aspiration after an upper endoscopic delivery of FMT was reported in 1 case as a complication of general anesthesia, suggesting there should be judicious evaluation of the merits of an upper FMT delivery in the setting of anesthesia and in CDI complicated by ileus.…”
Section: Safety Considerationsmentioning
confidence: 93%
“…The 3‐month mortality rates in the FMT group and the non‐FMT group were 12.1% and 42.2%, respectively. Early FMT reduced the mortality of FMT in severe CDI . So far, FMT offered broad spectral potential to treat CDI with high efficacy and minimal adverse events.…”
Section: Clinical Applicationmentioning
confidence: 99%